Rodenticide poisoning in a Toxicological Assistance Center - Beatriz Ferreira Martins; Anai Adario Hungaro; Jéssica Adrielle Teixeira Santos; William Campo Meschial; Laiane Mucio Correia; Magda Lúcia Félix de Oliveira (Rev Rene)
Objective: to characterize rodenticide poisoning sold illegally under the name Chumbinho. Methods: this is a descriptive and cross-sectional study by retrospective analysis of epidemiological forms of Toxicological Occurrence of a Toxicological Assistance Center, from 2006 to 2013. Results: 115 forms were analyzed, with an annual average of 14.4 ± 4.8 cases and 35.6% of the records in the fourth biennial. Most poisonings occurred in males (57.3%), aged between 15 and 49 years (78.3%) and suicide attempted (90.4%). It was found clinical severity of cases because 92.1% intoxicated required hospitalization and occurred four deaths (3.5%). Conclusion: the cases of poisoning by Chumbinho increased gradually over the studied years, in males, in an economically active age, and by intentional poisoning. There is a need for greater sanitary inspection in the region, aiming to reduce supply and improvement of guidance to consumers.